KEMAMPUAN MAHASISWA UNIVERSITAS KATOLIK MUSI CHARITAS DALAM MENGONVERSI TEKS - Tresiana Sari Diah Utami; Katarina Retno Triwidayati; Visinsia Mila Anggraini (STKIP Siliwangi, 2020)
Indonesian learning is carried out with various learning approaches. One of them is text based language learning approach or what is known as genre based text/ genre approach. One form of learning implemented using this approach is the activity of converting texts. This research method is qualitative research. The research was carried out at Musi Charitas Catholic University with a population of 382 writings and a sample of 180 random samples was determined. The study was conducted with pen and paper based text, which provides writing texts to students studied. The students studied were asked to read the predetermined news text, analyze the topics contained in the news, then write a simple essay text based on the results of the analysis. The student's writing is then assessed by two people and the final grade is determined by calculating the average of the scores of the two assessors. The results showed 67.2% of students studied were able to convert text from news texts into simple essay texts. While there are 13% of students who do not change the structure of their writing so that it can be stated that the student has not / converted the text.